Clinical outcomes of residual branch vessel dissection following type A aortic dissection repair - Jing Li; Siyuan Chen; Changying Zhao; Yang Yan (Frontiers in Medicine, 2026)
Objectives Although aortic arch replacement eliminates the primary entry tear in type A aortic dissection, residual dissection in arch branch vessels (RD-ABV), often linked to fragile distal tissue or residual tears, may sustain false lumen patency and be related to post-discharge recovery. The clinical relevance of RD-ABV remains unclear. Methods This retrospective cohort study included patients who underwent total arch replacement for aortic dissection between January 2018 and December 2024. Patients with in-hospital postoperative cerebral infarction, cerebral hemorrhage, or death were excluded, and follow-up began on the date of discharge. RD-ABV was assessed using the first postoperative CTA before discharge. The primary outcome was a composite event including modified Rankin Scale (mRS) 3–6, cerebral infarction (CI), cerebral hemorrhage (CH), and cardiovascular and cerebrovascular reoperation. Secondary outcomes included CI, CH, and reoperation. IPTW-adjusted win ratio was used for analyses of the primary and secondary composite outcomes. Results A total of 564 patients were included, of whom 156 had RD-ABV. The IPTW-adjusted win ratio of the primary composite outcome was 0.47 (95% CI: 0.27–0.82; P = 0.007), whereas the secondary composite outcome did not reach statistical significance (win ratio, 0.56; 95% CI: 0.30–1.08; P = 0.082). In IPTW-weighted Kaplan-Meier sensitivity analyses, lower event-free estimates were observed for the primary outcome (raw event-free counts, 123/156 [78.8%] vs. 355/408 [87.0%]; weighted log-rank P = 0.014), mRS 3–6 (133/156 [85.3%] vs. 387/408 [94.9%]; weighted log-rank P < 0.001), and CH (151/156 [96.8%] vs. 406/408 [99.5%]; weighted log-rank P = 0.034). No statistically significant differences were observed for the secondary composite outcome, CI, or reoperation. Hierarchical analyses indicated that the primary composite outcome was mainly driven by mRS 3–6. Conclusion Among selected post-discharge survivors after aortic arch replacement, RD-ABV was associated with worse mid-term functional recovery, mainly reflected by mRS 3–6. The secondary composite outcome excluding mRS did not reach statistical significance. These findings should be interpreted as hypothesis-generating and require prospective validation.